SOME APPLICATIONS OF THE PYTHAGOREAN THEOREM (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The Pythagoraean Theorem has been the driving force for the mathematical world since its discovery. It is generally credited to Pythagoras, a Greek mathematician even though archaeological evidence has stated that Babylonians, Egyptians, and Chinese people discovered it before him. It is because he was the first who revealed this theorem to the world by stating it clearly. The Pythagoras Theorem has many practical aspects as it has helped develop many tools and machinery, all of which have in some form shaped this developing world of ours. The theorem, which deals with the right-angled triangle, has also been used as a crucial base for many more laws. In this research paper, I have written many distinct ways, which we can use to prove the Pythagorean Theorem. These ways include the infamous Windmill proof (also known as bride’s chair proof) which was discovered by Euclid (another great Greek mathematician who has greatly helped the geometric world), the proof where we draw an altitude and use properties of similarity also called proof by similar triangles, Garfield’s proof which was discovered by James Garfield, the 20th US president and the proof using differentials which were earlier arduous to prove through.